An overview of pavement maintenance practice by local authority and government agency - Asma Aida, Amin Hafiz (2017)
Roads are one of the most important infrastructures in a community. A proper maintenance by road authority towards the road network can ease the business and daily activity of a community. The awareness among the authorities that handle the road pavement maintenance is very low. Proper and timely maintenance by road authorities is important for safety and comfort of users. The use of pavement maintenance management system provides significant benefits such as identification of the common problem in pavement maintenance, accurate prediction of road deterioration and improves the practices of pavement maintenance by road authorities from time to time. The research objective was to explore current practise of pavement maintenance management system in construction industry and to identify the common problems in pavement maintenance management system. By distributing the questionnaire that was directly being conducted with the road authorities from the government agency and local authorities from the maintenance and rehabilitation road department. The data collected were analyzed using an average index method and descriptive statistics to obtain the result. From the result, the current practice of pavement maintenance management system the most type of maintenance strategy chooses by local authority was 70% from ranking criteria and the least was 5% from HDM-4. From here, it shows that the staff preferred to do the maintenance strategy manually by using ranking criteria. it shows there were lacking of experience staff in local authority. This is because, HDM-4 needs an expert and experience staff to handle the software. As for the common problem in pavement maintenance management system, the average index for government agency in problem design stage was 3.5 which is neutral while for local authority was 3.45 which is neutral as well. For lack of controlling and monitoring by authority for government agency was 3.23 which is neutral while for local authority were 2.93 which is neutral as well. Next, funds for pavement maintenance for government agency were 3.83 which is agree while for local authority was 4 which is strongly agree. For communication and skill of the staff was 3.15 which is neutral while for local authority was 3.25 which is neutral as well. Next for training and understanding of staff for government agency was 3.88 which is agree while for local authority was 3.78 which is agree as well. From the result, we can see that the most common problem in pavement maintenance management system for government agency is training and understanding of staff. While the local authority is funds for pavement maintenance.